When prosthetic joint infection may lead to premalignant colorectal lesion detection - R. Posse, Julie; D. A. B. Werly, Thayná; Souza, Fabio; T. Cavanellas, Naasson; A. Matos, Juliana; B. G. Barbato, Kelly (International Journal of Research in Orthopaedics, 2023)
Osteoarthritis (OA) is a common musculoskeletal disorder that affects millions of people worldwide, and total knee arthroplasty (TKA) is a common treatment for advanced OA. However, joint replacement surgeries may lead to complications such as deep vein thrombosis (DVT), surgical site infection, and prosthetic joint infection (PJI). Our objective is to discuss a Streptococcus bovis group (SBG) PJI case after TKA and its possible consequences in clinical practice. We describe a 67-year-old female who underwent TKA and developed initial complications including wound hematoma, symptomatic anemia, and acute DVT. Further investigations because of knee pain persistence and inflammatory signs post TKA revealed the presence of Staphylococcus aureus in the synovial and scar tissues from the knee and SBG in the periprosthetic membrane from the revision surgery, as well as mitral infective endocarditis and a large stenosing villous polypoid lesion in the ascending colon. SBG osteoarticular infection post TKA is a rare condition, but it may be associated with severe diseases. This article highlights the link between SBG and colorectal cancer (CRC) and emphasizes the importance of an echocardiogram and a colonoscopy for early detection and prompt treatment of infective endocarditis and CRC. This diagnostic workup should be performed even in the absence of symptoms, for early diagnosis and increased chance of cure. A multidisciplinary approach, involving orthopedists, infectious disease specialists, cardiologists, and gastroenterologists, among others, is advised to effectively manage SBG infections and improve patient outcomes.